Analysing the Animal Euthanasia Scenario in India in Light of the Constitutional Provisions - Choudhary, Latika; Daga, Hardik (Christ University Law Journal, 2024)
When Mahatma Gandhi said that “the greatness of a nation can be judged by the way its animals are treated”, he clearly implied that equality must exist between the evolved animals, i.e. Humans and the rest of the animal clan. Humans have always adamantly self-proclaimed themselves as the ‘superior’ species, granting to themselves an authority to govern the rest, backed by a well-drafted constitution. While it is undeniable that a democratic society ensures fundamental rights to its citizens, a more civilized and sensitive one does not shy away from extending the same to its animals, too. The Apex Court of India in 2011 broke all barriers and differences in the famous Jallikattu case, whereby it brought animals under the ambit of the right to life guaranteed under Art. 21 of the Indian Constitution. While now this fundamental right has been constitutionally guaranteed to animals to live with dignity, a pertinent question to be asked is, does the right also encompass the right to die. The Supreme Court, in the case of Aruna Shanbaug, did declare that passive euthanasia is legal in India, thus bestowing the scope of passively ending the life of a terminally ill patient. Considering that animals may also very much be under the same circumstances, is this right of passive euthanasia applicable to them as well. This paper will thus dwell into analyzing the current scenario in India pertaining to euthanasia of ailing and terminally ill animals, the legal provision & judicial precedents worldwide on the issue and the moral rationale behind the same.